2
$\begingroup$

I would like to find the kernel of the following homomorphisms and show that thoses kernels have trivial intersection.

$H:=\mathbb{Z}*\mathbb{Z}/n\mathbb{Z}=\langle p,q| q^n=1\rangle$

$K=\mathbb{Z}^2=\langle c,d| cd=dc\rangle$

$G:=BS(n,n)=\langle a,b| ba^nb^{-1}=a^n\rangle$

$\phi_1 :G\rightarrow H$ defined by $\phi_1(a)=q$ and $\phi_1(b)=p.$

$\phi_2 :G\rightarrow K$ defined by $\phi_1(a)=c$ and $\phi_1(b)=d.$

It is easy to see that ker($\phi_1)\leq\langle b^ka^nb^{-k} \mid k \in {\mathbb Z} \rangle.$ I wonder if this is an equality.

If $g=a^{k_1}b^{l_1}\dots a^{k_r}b^{l_r}\in G$ with $k_1,\dots,k_r,l_1,\dots, l_r\in\mathbb{Z}$, then I proved that $g\in$ ker($\phi_2$) if $k_1+\cdots k_r=0$ and $n$ divides $l_1+\cdots+l_r.$ Is there a better description of ker($\phi_2$)? By advance thank you.

$\endgroup$
5
  • 2
    $\begingroup$ But $b^ka^nb^{-k} = a^n$. In fact $\langle a^n \rangle = Z(G)$ and this is the kernel of $\phi_1$. What you have written about $\ker(\phi_2)$ does not look right because $\phi_2(b^n)=d^n \ne 1$. In fact $\ker(\phi_2) = [G,G]$ and it is true that $\ker(\phi_1) \cap \ker(\phi_2)=1$. $\endgroup$ – Derek Holt Jul 23 '15 at 16:17
  • $\begingroup$ But how do I prove ker($\phi_1)\leq\langle a^n\rangle$ and ker($\phi_2)\leq[G,G]$? $\endgroup$ – Edgar Ndie Jul 24 '15 at 12:13
  • $\begingroup$ See my answer below. $\endgroup$ – Derek Holt Jul 24 '15 at 12:45
  • $\begingroup$ I would like to do the same thing for $BS(n,-n)$ i.e find the kernel of $\phi_1' :BS(n,-n)\rightarrow H$ defined by $\phi_1'(a)=q$ and $\phi_1'(b)=p$ but there is a problem. Ok We still have that $N \le \ker(\phi_1')$ where $N$ is still the normal closure of $\langle a^n\rangle$ since $a^n\in\ker(\phi_1'),$ but I think in the case of $BS(n,-n),$ $N\neq\langle a^n\rangle$ since $a^n$ and $b$ don't commute in this case. So in this case wat is the kernel of $\phi_1'?$ $\endgroup$ – Edgar Ndie Aug 3 '15 at 7:43
  • $\begingroup$ I would also like to find the kernel of $\phi_2':BS(n,-n)\rightarrow BS(1,-1)=\langle c,d| dcd^{-1}=c^{-1}\rangle$ defined by $\phi_2'(a)=c$ and $\phi_2'(b)=d.$ Again $N'\leq\ker(\phi_2')$ wher $N'$ is the normal closure of $bab^{-1}a$ since $bab^{-1}a\in\ker(\phi_2').$ But is $N'$ equal to $\langle bab^{-1}a\rangle?$ Because if if it's the case, then in using your method below, we'll have $\ker(\phi_2')=\langle bab^{-1}a\rangle.$ By advance thank you. $\endgroup$ – Edgar Ndie Aug 3 '15 at 7:56
2
$\begingroup$

Clearly $a^n \in \ker(\phi_1)$. So $N \le \ker(\phi_1)$, where $N$ is the normal closure of $\langle a^n \rangle$ in $G$. But in fact, since $a^n$ is centralized by both $a$ and by $b$, we have $a^n \le Z(G)$, so $N = \langle a^n \rangle$.

So $\phi_1$ induces a homomorphism $\bar{\phi}_1: G/N \to H$. But $$G/N = \langle a,b \mid b^{-1}a^nb=a^n, a^n=1 \rangle = \langle a,b \mid a^n=1 \rangle$$ and hence $\bar{\phi}_1$ is an isomorphism, so $N = \ker(\phi_1)$.

The proof that $\ker(\phi_2) = [G,G]$ is similar, because $$G/[G,G] = \langle a,b \mid b^{-1}a^nb=a^n, ab=ba \rangle = \langle a,b \mid ab=ba \rangle.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.